PENANGGULANGAN KEMISKINAN PADA PETANI BERLAHAN SEMPIT DI AGROEKOSISTEM LAHAN KERING DATARAN TINGGI BERBASIS SAYURAN - AMAR K. ZAKARIA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2005)
Poverty Alleviation for Small Scale Farmers in Horticulture Based Upland. The strategyof Agricultural development is directed to improve the income of farmers and ruralsociety, especially small scale farmers. This study was conducted in upland area of AgamDistrict, West Sumatera. The dominant crops cultivated in this area were horticulture,mainly vegetables. The results of the study showed that agricultural sector contributedabout 89.2 percent of household income for the good access area and about 67.8 percentfor the poor access area. Based on the status and stability of income, the results showedthat the medium income level had a high stability.